2022
DOI: 10.1101/2022.09.26.509516
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Activity-based directed evolution of a membrane editor in mammalian cells

Abstract: Cellular membranes contain numerous lipid species, and efforts to understand the biological functions of individual lipids have been stymied by a lack of approaches for controlled modulation of membrane composition in situ. Here, we present a strategy for editing phospholipids, the most abundant lipids in biological membranes. Our membrane editor is based upon a bacterial phospholipase D (PLD), which exchanges phospholipid head groups through hydrolysis or transphosphatidylation of phosphatidylcholine with wat… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…When both constructs are expressed in mammalian cells, CRY2–CIBN heterodimerization upon blue-light stimulation recruits PLD to the desired membrane to produce PA (Figure B). OptoPLD enabled PA generation on several organelle membranes, including the PM, endosomes, the endoplasmic reticulum (ER), and the trans-Golgi network in our initial study and in subsequent work additional organelles such as mitochondria and lysosomes . To demonstrate the biological relevance of the optoPLD-derived PA, we established that PM-targeted optoPLD caused translocation of YAP into the nucleus under starvation, providing evidence of a suppressive effect of PM pools of PA on Hippo signaling.…”
Section: An Optogenetic Phospholipase D Enables Spatiotemporally Cont...mentioning
confidence: 85%
See 4 more Smart Citations
“…When both constructs are expressed in mammalian cells, CRY2–CIBN heterodimerization upon blue-light stimulation recruits PLD to the desired membrane to produce PA (Figure B). OptoPLD enabled PA generation on several organelle membranes, including the PM, endosomes, the endoplasmic reticulum (ER), and the trans-Golgi network in our initial study and in subsequent work additional organelles such as mitochondria and lysosomes . To demonstrate the biological relevance of the optoPLD-derived PA, we established that PM-targeted optoPLD caused translocation of YAP into the nucleus under starvation, providing evidence of a suppressive effect of PM pools of PA on Hippo signaling.…”
Section: An Optogenetic Phospholipase D Enables Spatiotemporally Cont...mentioning
confidence: 85%
“…OptoPLD enabled PA generation on several organelle membranes, including the PM, endosomes, the endoplasmic reticulum (ER), and the trans-Golgi network in our initial study 3 and in subsequent work additional organelles such as mitochondria 32 and lysosomes. 33 To demonstrate the biological relevance of the optoPLD-derived PA, we established that PM-targeted optoPLD caused translocation of YAP into the nucleus under starvation, providing evidence of a suppressive effect of PM pools of PA on Hippo signaling. Interestingly, this finding not only corroborated a previous study indicating that PA can antagonize the Hippo pathway 24 but also concluded that PA generated at the PM and not on other organelle membranes is the main driver of this phenotype, driving home the importance of spatial regulation of PA-dependent signaling.…”
Section: Spatiotemporally Controlled Pa Productionmentioning
confidence: 99%
See 3 more Smart Citations